2001
DOI: 10.1097/00007632-200111010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Transforming Growth Factor-Beta 1 in Ligamentum Flavum of Lumbar Spinal Stenosis and Disc Herniation

Abstract: The current results suggest that higher expression of TGF-beta1 by fibroblasts might be related to the development of hypertrophy of the ligamentum flavum in lumbar spinal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 23 publications
7
137
0
2
Order By: Relevance
“…We previously demonstrated the expression of transforming growth factor-beta 1 (TGF-β1) in ligamentum flavum fibroblasts and found that the concentration was significantly higher in patients with spinal stenosis than it was in patients with disc herniation 28 . In an in vitro study, Nakatani et al found that mechanical stretching force promotes collagen synthesis by cultured cells from human ligamentum flavum tissues through increased TGF-β1 production 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated the expression of transforming growth factor-beta 1 (TGF-β1) in ligamentum flavum fibroblasts and found that the concentration was significantly higher in patients with spinal stenosis than it was in patients with disc herniation 28 . In an in vitro study, Nakatani et al found that mechanical stretching force promotes collagen synthesis by cultured cells from human ligamentum flavum tissues through increased TGF-β1 production 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Quite likely, cells extracted from hernia tissue are a mixed population of nucleus pulposus, annulus fibrosus and other various cell types from the external periphery (Brock et al, 1992;Harada et al, 1989;Willburger et al, 2004). During the period preceding hernia resection, this tissue will experience unusual loading conditions and potential inflammatory responses (Ikeda et al, 1996;Park et al, 2001). The increased inflammatory factors may have highly negative or fibrotic influence on the phenotype of the cells isolated from this herniation tissue, reflecting markers of degeneration.…”
Section: Continuous Expansion Culture Of Np Cellsmentioning
confidence: 99%
“…16 We measured the thickness of the ligamentum flavum three times and used the average of the three repeated measurements as the final value.…”
Section: Magnetic Resonance Imaging Of the Ligamentum Flavummentioning
confidence: 99%